2012
DOI: 10.1111/j.1651-2227.2012.02603.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep problems in children with cerebral palsy and their relationship with maternal sleep and depression

Abstract: Children with cerebral palsy have more sleep problems than typically developing peers. Their mothers also have disturbed sleep that correlates with maternal depression. Childhood sleep problems can be treated and should be identified in routine clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
105
3
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(123 citation statements)
references
References 29 publications
9
105
3
6
Order By: Relevance
“…The schedule demands of parent employment and school attendance may impact parent sleep and daily T1D management behaviors. Child sleep concerns have been shown to relate to parent sleep disruption, daytime sleepiness, and worse psychosocial functioning among healthy populations and chronic illness populations such as cerebral palsy (Boergers, Hart, Owens, Streisand, & Spirito, 2007; Wayte, McCaughey, Holley, Annaz, & Hill, 2012). Although the limited extant literature regarding sleep among young children with T1D suggests that children may experience typical sleep patterns, it also indicates that bedtime concerns and child insomnia are related to greater parent psychosocial functioning concerns, including stress, anxiety, and depression (Monaghan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The schedule demands of parent employment and school attendance may impact parent sleep and daily T1D management behaviors. Child sleep concerns have been shown to relate to parent sleep disruption, daytime sleepiness, and worse psychosocial functioning among healthy populations and chronic illness populations such as cerebral palsy (Boergers, Hart, Owens, Streisand, & Spirito, 2007; Wayte, McCaughey, Holley, Annaz, & Hill, 2012). Although the limited extant literature regarding sleep among young children with T1D suggests that children may experience typical sleep patterns, it also indicates that bedtime concerns and child insomnia are related to greater parent psychosocial functioning concerns, including stress, anxiety, and depression (Monaghan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…ve Önes ve ark. çalışmalarında çocukta spastisite ve fonksiyonel seviye ile annenin depresyonu arasında anlamlı bir ilişki saptanmamıştır (15,17,18). Zihinsel ve/veya bedensel özürlü çocukların değerlendi-rildiği, Şenveli ve ark.nın çalışmasında annelerin depresyon düzeylerinde anlamlı bir farklılık bildirilmemiştir (19).…”
Section: Discussionunclassified
“…SP'li çocuklardaki hareket bozukluğu ve buna eşlik eden hareket bozukluğu dışındaki problemler hastanın ve hastaya sürek-li bakım veren kişinin (sıklıkla annenin) yaşam kalitesini etkilemektedir (5). Çocuğun bakıma ihtiyaç duyması ve ek problemleri nedeniyle bakım veren kişi duygu durum bozukluğu ve tükenmişlik açısından risk altında olup bakıcı yükünü etkileyen önemli faktörlerden biri de çocuğun uyku düzenidir (6).…”
Section: Introductionunclassified
“…It is known that there are difficulties in beginning and sustaining sleep, irregular sleep and wakefulness transitions, respiratory problems related to sleep and an increased state of sleepiness in children with CP [33]. Kılıc et.…”
Section: Discussionmentioning
confidence: 99%
“…Although about 5% sleep disorder has been observed in children who display normal growth and development, studies have shown that there is a much higher rate of sleep problem in children with CP [9]. In children with CP, insufficiency in starting and sustaining sleep, irregular sleep-wakefulness transitions, respiratory difficulties related to sleep and increased day time sleepiness have been reported [10].…”
Section: Introductionmentioning
confidence: 99%